PENINGKATAN KEJADIAN PRESBIKUSIS PADA LANSIA HIPERTENSI DI PUSKESMAS KURAI TAJI PARIAMAN TAHUN 2021 - Triansyah, Irwan; Darmayanti, Anita; Sari, Desi Permata (Nusantara Hasana Journal, 2022)
Presbycusis is a decrease in hearing function that follows the ageing process. One of the risk factors for presbycusis is hypertension. Hypertension can cause rupture of blood vessels in the inner ear and cause sudden hearing loss. In addition, hypertension can cause reduced blood flow resulting in tissue hypoxia resulting in hearing complaints.The purpose of the study was to determine the relationship between hypertension and the incidence of presbycusis in the elderly at the Kurai Taji Pariaman Health Center in 2021. The type of research is unpaired categorical analytic research with a case-control design using primary data. The affordable population used in this study were the elderly who came for treatment at the Kurai Taji Health Center during the study period, with 39 samples that met the inclusion and exclusion criteria using a consecutive sampling technique. The results of this study were that most presbycusis patients were found in the age group of 60-70 years (60.6%), and the sex of most presbycusis patients was women. Most patients with presbycusis have grade 2 hypertension. The relationship between hypertension and the incidence of presbycusis is obtained p-value = 0.000. The conclusion of the study is that there is a relationship between hypertension and the incidence of presbycusis in the elderly at the Kurai Taji Pariaman Health Center in 2021.